2022
DOI: 10.1002/dad2.12321
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and renal function impact concentrations of plasma biomarkers of neuropathology

Abstract: Introduction The impact of hepatorenal function on plasma biomarkers of neuropathology is unknown. Herein, we measured several plasma biomarkers in patients with cirrhosis. Methods Plasma phosphorylated tau (p‐tau181), neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), total tau (t‐tau), and ubiquitin carboxyl‐terminal hydrolase L1 (UCHL1) were measured in 135 adults with cirrhosis and 22 healthy controls using Simoa. Within cirrhosis, associations between biomarkers and hepatorenal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 15 publications
3
33
1
Order By: Relevance
“…Recent studies also found that cirrhosis, history of stroke, and myocardial infarction is associated with increased plasma p‐tau181. 9 , 10 Such associations cannot be evaluated in our small study. Finally, due to the design, we cannot obtain the baseline cognitive performance in this population.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Recent studies also found that cirrhosis, history of stroke, and myocardial infarction is associated with increased plasma p‐tau181. 9 , 10 Such associations cannot be evaluated in our small study. Finally, due to the design, we cannot obtain the baseline cognitive performance in this population.…”
Section: Discussionmentioning
confidence: 77%
“…We also found an unequivocal negative correlation between plasma p‐tau181 and kidney function, which is consistent with previous reports. 9 , 10 Indeed, plasma p‐tau can reach several fold of the cut‐off values in non‐AD patients with severe kidney dysfunction. Nonetheless, impaired renal clearance cannot explain all false positive cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is consistent with recent observations that plasma p-tau217 concentrations are influenced by non-neurodegenerative comorbidities, including renal and hepatic diseases. [33][34][35] These factors could result in plasma-specific measurement error that would weaken associations with other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Berry et al. examined the influence of liver cirrhosis and biomarker evidence of kidney dysfunction on blood concentrations of AD‐related biomarkers 6 . Windon et al.…”
mentioning
confidence: 99%